Parametric study of immersion-Sn plating on Cu effect on reaction kinetics and porosity of deposit - Fajardo, Charlene Jovita I.
Immersion-Sn is a Pb-free final finish that combines the low cost and process simplicity of organic solderability preservative (OSP) and the surface conductivity of electroless nickel immersion gold (ENIG). It deposits a thin, uniform, and planar Sn layer on Cu following an ion-replacement mechanism that consumes the substrate in-reaction. The process is self-limiting, which means that the reaction stops when the Sn film is thick enough to hinder the reaction. This research aims to determine the deposition kinetics of immersion Sn and to identify the main and interaction effects of plating time, temperature and bath agitation to both thickness and porosity of deposit.